Short komunication: Greater crested tern (Thalasseus bergii) population on the South Coast of Getem, Jember, Indonesia - abdu rohman (Aceh Journal of Animal Science, 2023)
Greater crested tern (Thalasseus bergii) is one of the settler and migratory seabirds. Habitat beach and rest on the shore with other groups of terns. This study aimed to determine the population of Thalasseus on the southern coast of Getem Jember. They are using the encounter rates method. Bird watching in the morning from 06.00-08.00 and afternoon from 15.30-17.30. Recording data on species, number of birds, and other supporting data. Identification using the book Mac Kinnon et al., 2010, Bhushan, B., et al., 1993. Using monocular binoculars, camera, and global positioning system support tools. Analysis of bird species' density index data utilizing the formula Alikodra 1990. Thalasseus bergii were 413 individuals. The results of the Estuary analysis are the locations with the highest number of other survey locations.Keywords: Population, Thalasseus bergii, South Coast of Getem, Jember.